2019
DOI: 10.3390/en12112098
|View full text |Cite
|
Sign up to set email alerts
|

Optimization-Based Control Concept with Feed-in and Demand Peak Shaving for a PV Battery Heat Pump Heat Storage System

Abstract: The increasing share of renewable energies in the electricity sector promotes a more decentralized energy supply and the introduction of new flexibility options. These flexibility options provide degrees of freedom that should be used optimally. Therefore, in this paper, a model predictive control-based multi-objective optimizing energy management concept for a hybrid energy storage system, consisting of a photovoltaics (PV) plant, a battery, and a combined heat pump/heat storage device is presented. The conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The simple and commonly used priority-based EM usually provides the best results with regard to the degree of self-sufficiency of a PVBSS [12,14]. However, rule-based EM concepts cannot be used for more complex EM tasks, such as the multi-objective optimization [15] discussed in this paper, or the management of hybrid energy storage systems [16], since an analytical derivation of an optimal control policy is not practical for these cases.…”
Section: A1 Energy Management For Pv Battery Storage Systemsmentioning
confidence: 99%
“…The simple and commonly used priority-based EM usually provides the best results with regard to the degree of self-sufficiency of a PVBSS [12,14]. However, rule-based EM concepts cannot be used for more complex EM tasks, such as the multi-objective optimization [15] discussed in this paper, or the management of hybrid energy storage systems [16], since an analytical derivation of an optimal control policy is not practical for these cases.…”
Section: A1 Energy Management For Pv Battery Storage Systemsmentioning
confidence: 99%
“…For heat pumps applications, relevant research includes cost-optimized sizing strategies [42,43] and optimization-based model predictive control [44]. Some works even study heat pumps in elec-tric vehicles for combined space and battery cooling [45].…”
Section: Prior Work In Distributed Storagementioning
confidence: 99%
“…The authors found that the smart control strategy can contribute to 26.4% of final energy reduction, 60% of the self-consumption increase and 15% of the net annual electricity cost reduction compared to the case with independent PV and heat pump. Similarly, a predictive control-based multi-objective optimization energy management concept was proposed for a PV system combined with heat pumps, heat storage, and batteries [89]. This concept was designed to reduce operational costs and power exchange with the power grid while ensuring comfort for the user.…”
Section: System Optimisationmentioning
confidence: 99%